Pharmacotherapy for treatment-resistant schizophrenia - Meghan E Mcilwain (Dove Medical Press, 2011)
Meghan E Mcilwain1,2, Jeff Harrison1, Amanda J Wheeler1,3, Bruce R Russell1,21School of Pharmacy, Faculty of Medical and Health Sciences, University of Auckland, Auckland, New Zealand; 2Centre for Brain Research, Faculty of Medical and Health Sciences, University of Auckland, Auckland, New Zealand; 3School of Human Services, Griffith University, Queensland, AustraliaAbstract: Schizophrenia is a disabling mental illness with a lifetime prevalence of 0.7% worldwide and significant, often devastating, consequences on social and occupational functioning. A range of antipsychotic medications are available; however, suboptimal therapeutic response in terms of psychotic symptoms is common and affects up to one-third of people with schizophrenia. Negative symptoms are generally less amenable to treatment. Because of the consequences of inadequate symptom control, effective treatment strategies are required for people with treatment-resistant schizophrenia. Clozapine has been shown to be more effective than other antipsychotics in treatment-resistant populations in several studies; however, the occurrence of adverse effects, some of which are potentially life-threatening, are important limitations. In addition to those who are intolerant to clozapine, only 30% to 50% experience clinically significant symptom improvement. This review describes the recent evidence for treatment strategies for people not responding to nonclozapine antipsychotic agents and people not responding or only partially responding to clozapine.Keywords: antipsychotic, refractory, clozapine